THE INFLUENCE OF LEARNING STRATEGIES FOR CONCEPT MAPS AND THINKING STYLES ON THE LEARNING OUTCOMES OF ISLAMIC RELIGIOUS EDUCATION AND ETHICS - Syamsu Nahar, Sudartik, Candra Wijaya, (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2021)
Abstract: The learning strategies used by teachers so far have not been optimal, causing student boredom which results in low learning outcomes. This study used an experimental method with a quasi-experimental design with a 2 x 2 factorial design. Through this design, the effect of concept map and expository learning strategies on the learning outcomes of Islamic Religious Education and Student Characteristics was compared to the students. The population of this research was all class IV SD Negeri 112256 Sabungan, Sungai Kanan District, South Labuhanbatu Regency which consisted of 3 classes. Each class in the population has the same characteristics, meaning that each class does not have students who have lived in class, the average student has an age that is not significantly different, using the same educational curriculum. In addition, class division is not carried out based on incoming ranking, so that there are no superior classes with different student characteristics. The sampling technique in this study was a cluster random sampling technique, ie from 3 classes 2 classes were selected as samples subject to treatment through random selection. The findings of this study are: First, based on the calculation of ANOVA, it turns out that the value of F-count = 27.44> F-table = 3.98 so that it can be concluded that the learning outcomes of Islamic Religious Education and Characteristics of students taught by concept map learning strategies are higher than with the learning outcomes of Islamic Religious Education and the character of students who are taught with expository learning strategies that are proven true. Second, based on the calculation of ANOVA, it turns out that the value of F-count = 6.17> F-table = 3.98 so that it can be concluded that the learning outcomes of Islamic Religious Education and Characteristics of students with a sequential thinking style are higher than the learning outcomes of Islamic Religious Education and The character of students with random styles thinking is verified. Third, based on the calculation of ANOVA, it turns out that the value of F-count = 18.27> F-table = 3.98 so that it can be concluded that there is an interaction between learning strategies and thinking styles in influencing the learning outcomes of Islamic Religious Education and student's character is proven.